INFLUENCE OF NITRIDING PROCESS VARIABLES ON THE TENSILE STRENGTH OF AUSTENITIC STAINLESS STEEL 316L - HARUN, MUHAMMAD ERMAN (IRC, 2017)
This project is to describe the tensile strength of nitride layer of the material. The specimen used in describing the material strength is the Austenitic Stainless Steel (316L). The Austenitic Stainless Steel 316L specimens will be nitride with the different parameters and undergo the experiment in order to obtain the properties of the material strength. The exposure of Austenitic Stainless Steel into the gas nitriding at 400°C and 1200°C with fixed pressure with 8 hours of expose. The microstructure of the austenitic stainless steel 316L studied based on the gas nitriding temperature variables where Nitrogen (N2) gas used as a nitriding gas. The sample of the nitrided will be undergoing tensile test for the mechanical performance.The condition of layer of the gas nitriding after being nitrided and undergo testing to identify the microsructure using scanning electron microscope (SEM). The process of Scanning Electron Microscopy (SEM) required in identifying the microstructure of the nitirided Austenistic Stainless Steel with different condition.